High resolution zone location time series in Japanese quail in a home-cage environment over a 6.5 day period (ALL SERIES) - Kembro, Jackelyn Melissa (2015)
Fil: Kembro, Jackelyn Melissa. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.